SOCIAL ANALYSIS OF THE TRANSFORMATION OF RELIGIOUS PRACTICES IN CONTEMPORARY MUSLIM SOCIETY - Aditya Rahmatullah; Fatimah Zahra (STAI Sebelas April Sumedang, 2022)
Abstract This study examines the transformation of religious practices within contemporary Muslim communities, focusing on the impact of modernization, digitalization, and globalization. Using a qualitative research approach, including in-depth interviews, participant observation, and digital media analysis, the study explores how these forces reshape traditional religious practices and identities. The findings reveal that while many Muslims have embraced digital tools such as religious apps and social media to enhance their worship, conservative groups resist these changes, viewing them as threats to religious authenticity. Additionally, the research highlights the emergence of transnational Islamic networks that facilitate cross-cultural exchanges and shape global Muslim identities. This dynamic interplay between tradition and modernity offers insights into how Muslim communities negotiate their religious values in an increasingly interconnected world. The study contributes to the broader understanding of religious adaptation in the digital age and suggests areas for further exploration regarding generational responses to these changes.